The effects of experiential learning on teaching perception and learning approaches among public relations students - Teoh, Hee Chong; Yap, Teng Teng (Taylor's University College, 2018)
The public relations practice in Malaysia has received criticism for not reaching the level of sophistication and development of its overseas counterparts. In view of this, higher education institutions that offer public relations courses in Malaysia have continuously been involved in efforts to improve the occupational standing and prestige of the public relations industry. This study aims to examine the effects of experiential learning practices on teaching perception and learning approaches among public relations students. The current study implemented an action research with a causal-comparative research design. Two cohorts of public relations students with 36 students for 2014 and 58 students for 2015 Bachelor’s degrees were selected to investigate the effects of experiential learning teaching design on students’ perception of teaching and their approaches to learning. The findings of the study indicated that experiential learning has positive impacts on both the teaching perceptions and the learning approaches selected by the students. Overall, students who were exposed to the experiential learning teaching approach had a greater tendency to apply a deep approach in their learning compared with those who learn in the context of the traditional lecture-plus-discussion classroom. In addition, the students showed more interest, were more engaged, and demonstrated more willingness to learn in the experiential learning classroom. The findings of the study suggest that experiential learning could be embedded into the curricula of public relations courses. Students’ learning can ultimately be enhanced by incorporating a suitable assessment approach and teaching strategies that highlight experiential learning.